The created stone: chemical and archaeological perspectives on the colour and material properties of early Egyptian glass, 1500-1200 B.C. - Duckworth, Chloë N. (2011)
The Late Bronze Age in Western Asia and Egypt witnessed an explosion in the production of so-called 'vitreous materials', in particular the earliest glass. From its outset, this material appeared in an enormous variety of colours and colour combinations, the manufacture of which demanded a high degree of technological know-how. The unique properties of glass also rapidly came to the fore, most notably the potential of glass to be worked while hot.